2003
DOI: 10.1118/1.1587431
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study on epithermal neutron field for cyclotron‐based boron neutron capture therapy

Abstract: To realize the accelerator-based boron neutron capture therapy (BNCT) at the Cyclotron and Radioisotope Center of Tohoku University, the feasibility of a cyclotron-based BNCT was evaluated. This study focuses on optimizing the epithermal neutron field with an energy spectrum and intensity suitable for BNCT for various combinations of neutron-producing reactions and moderator materials. Neutrons emitted at 90 degrees from a thick (stopping-length) Ta target, bombarded by 50 MeV protons of 300 microA beam curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…1, the measured neutron energy spectrum for the Ta(p,n) reaction is compared with the calculations using the LA150 cross section data. 6) As shown in this figure, the calculation overestimates the measurement by a factor of about three in the energy range higher than $5 MeV.…”
Section: Influence Of La150 Datamentioning
confidence: 89%
See 2 more Smart Citations
“…1, the measured neutron energy spectrum for the Ta(p,n) reaction is compared with the calculations using the LA150 cross section data. 6) As shown in this figure, the calculation overestimates the measurement by a factor of about three in the energy range higher than $5 MeV.…”
Section: Influence Of La150 Datamentioning
confidence: 89%
“…10) The experimental setup shown in Fig. 1 Comparison of the measured neutron energy spectrum for the Ta(p,n) reaction at 90 bombarded by 50-MeV protons with the calculation using the LA150 cross section data library 6) a As written in Ref. 9), we used the LA150 data of the W(p,n) reaction instead of the Ta(p,n) reaction, because the LA150 data does not include the Ta(p,n) reaction.…”
Section: Influence Of La150 Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Some design studies of accelerator-based epithermal neutron generators for BNCT [4][5][6][7][8][9][10][11] showed that an irradiation treatment took a half hour or more at the level of epithermal neutron flux obtained with the available proton current by using the latest state-of-the-art technology. Experience has shown that it is difficult to keep a patient motionless over a treatment period lasting more than a half hour.…”
Section: Introductionmentioning
confidence: 99%
“…8) Tantalum can be used as an alternative target material to W because the characteristics of neutron production are similar. 9) A thick W target has the advantage of a lower ratio of high-energy neutron production to total neutrons than a thick Be target. On the other hand, a thick Be target has the advantage of larger total neutron production than a thick W target.…”
Section: Introductionmentioning
confidence: 99%